Vision 2010 a strategic plan for Prime Breed, Inc. - Teves, Elizabeth R.; Concepcion, Sylvia B.; Soledad, Miguel D. (Davao City School of Management, University of the Philippines Mindanao, 2006)
Vision 2010 is a blueprint which aims to steer the strategic directions of the company in the next five years. The goal is for PBI to achieve not only profitability and growth but also carve a dominant position in the livestock industry. After forty four years of existence in the agribusiness, Prime Breed, Inc., has reached maturity after undergoing growth and decline stages in its life cycle. From humble beginnings in the early sixties, the So family propelled the company to the growth and banner years if the seventies and eighties. PBI surpassed the test of time when it hurdled the challenging years following the Asian financial crisis. PBI pulled through and has undoubtedly made a mark of stability and survival. But as one author would say, successful organizations need to change direction not in order to survive but to maintain their success. The challenge now for PBI is to untangle itself from the status quo with the introduction of this five-year strategic plan. This will definitely entail organizational-wide support and commitment in order to achieve the company's objectives. From the current turnaround and best-cost strategy, this plan presents strategic initiatives that will reposition PBI to be a low cost provider and achieve growth through a two-pronged approach of market penetration and product development. It will also explore diversification moves by entering into joint venture with real estate developers with the aim of maximizing its valuable resources. Further improvements on its core business can be achieved with the strengthening of a marketing orientation, a leveraging of PBI's core competencies and strategic alliance with A-1 Pigs, PBI's foreign partner. A conservative posture of cost and debt reduction will also be adopted in order to achieve a sound financial position. With the transition from the first generation to the young breed of proactive management team, PBI is undergoing major transformations starting with the institutionalization of its vision and mission statements, setting of clear goals and objectives, reinforcing policies, incentives and other internal support systems. The successful implementation of this strategic plan hinges on an effective monitoring and control system and adherence to a high performance culture coupled with effective management of change, reengineering and continuous improvement.
Thesis, Graduate (Master in Management)--University of the Philippines Mindanao, March 2006.